Coronavirus disease 2019 (COVID-19) can predispose young to Intracerebral hemorrhage: a retrospective observational study - Michael T. Lawton; Ehsan Alimohammadi; Seyed Reza Bagheri; Arash Bostani; Siavash Vaziri; Ali Karbasforoushan; Kossar Mozaffari; Mehran Bahrami Bukani; Alireza Abdi (BMC Neurology, 2021)
Abstract Background The respiratory system involvement is the most common presentation of Coronavirus disease 2019 (COVID-19). However, other organs including the central nervous system (CNS) could be affected by the virus. Strokes, seizures, change in mental status, and encephalitis have been reported as the neurological manifestation of the disease. We hypothesized that COVID-19 could predispose younger patients to spontaneous intracerebral hemorrhage (ICH). The present study aimed to investigate whether COVID-19 has any relationship with the occurrence of spontaneous ICH in young or not. Methods We retrospectively evaluated all the patients with spontaneous ICH who were referred to our center between 20 Feb and 1 Sep 2020. The demographic, clinical, radiological, and laboratory test data were evaluated. Patients were divided into two groups. The COVID-19 positive patients and COVID-19 negative ones. All the variables including age, sex, history of hypertension, diabetes mellitus, smoking, Glasgow Coma Scale (GCS), hematoma volume and location, the presence of intraventricular hemorrhage and hydrocephalus on admission, the length of hospital stay, the lab test results and the clinical outcome at last visit or discharge as Glasgow Outcome Scale (GOS) were compared between the two groups. Results There were 22 COVID-19 positive patients (20.8%) and 84 COVID-19 negative ones (79.2%). The mean age of the patients in the case group (54.27 ± 4.67) was significantly lower than that in the control group (69.88 ± 4.47) (p < 0.05). Meanwhile, our results showed a significant difference between the two groups based on the presence of chronic arterial hypertension (p < 0.05). There were no significant differences between the two groups based on gender, diabetes mellitus, smoking, Glasgow Coma Scale (GCS), hematoma volume, need for surgery, the presence of intraventricular hemorrhage and hydrocephalus on admission, White Blood Cell (WBC) count, platelet count, Prothrombin Time (PT), and Partial Thromboplastin Time (PTT) (p > 0.05). Conclusions Our results show that COVID positive patients with ICH are younger and with less predisposing factors than COVID negative subjects with ICH.